Narrative keys in the tradition «With days and pots overcome". Fiction as permanent reality - Pantigoso Pecero, Manuel (2023)
The article shows the contributions of the Ricardo Palma Institute, through the analysis of the tradition “ Con días y ollas venceremos” (“We will win with days and pots”): the well-known historical paragraph, the description of the Lima proclamations and the meaning of the santo y seña. The reader is then invited to recognize the keys and clues left by the traditionist, making a parallelism between military strategy and the phenomenon of literary creation. Thus, the palmist narrative procedures are highlighted, especially those that correspond to the art of hiding or cheating, the suggestion and appetence of the verbal game, the modern concept of history through fiction and the blending of other elements to enhance the idea of time, space and the atmosphere of the narration. In the end the riddle appears solved with touches that announce the marvelous reality. Keywords: riddle, strategies, suspense, fiction, modernity